MANAJEMEN MADRASAH IBTIDAIYAH DI KABUPATEN LEBONG - Evi Erlina (Manajer Pendididikan, 2016)
The objective of this research was to describe about  management of state Madrasah Ibtidaiyah. The research method was designed as qualitative descriptive. The subject of this research were head master, teacher, schoolquard, student’s, parents and documents. The technique of collecting data were observation, interview, and documentation. Data analysis technique included data reduction, data display, and conclusion verification. The Research concluded that planning the programs had supported school activities, posting teachers were relevant to their educational background, developing curriculum with effective and efficient, participating students the determining activities available to their talent, competence, and motivations, budgeting school finance in every year by participating all school components that they were authorized to control financial use, using school facilities and tools to support learning process, participating parents in arranging schools.Keywords: management, Madrasah Ibtidaiyah